Hubungan Keikutsertaan Senam Hamil dengan Tingkat Kecemasan Pada Primigravida Trimester III di BPM Widiasih - Kadek Yoga Wiratama; I Made Pariartha; Anny Eka Pratiwi (Fakultas Ilmu Kedokteran dan Ilmu Kesehatan, Universitas Warmadewa, 2024)
Anxiety levels during pregnancy can fluctuate as in the first trimester, anxiety begins to occur, then decreases in the second trimester, and increases again in the third trimester. Anxiety during pregnancy until the third trimester if not addressed immediately will have an impact on fetal growth and development, increase in MMR (Maternal Mortality Rate) and IMR (Infant Mortality Rate), can cause premature birth, low birth weight (LBW), old age labor, as well as mental and motor disorders of children. Anxiety due to pregnancy tends to often occur in primigravida due to pregnancy and childbirth because they have never experienced something similar. The purpose of this study was to determine the relationship between participation in pregnancy exercise and anxiety levels in third trimester primigravida mothers at IPM (Independent Practice Midwife) Widiasih, Batubulan region, Gianyar in the face of childbirth. This research uses analytical research method with cross sectional study design. Sampling in this study using accidental sampling technique and total sampling method. The sample consisted of 55 third trimester primigravida mothers who had met the inclusion and exclusion criteria. The data collection instrument used the HARS (Hamilton Rating Scale for Anxiety) questionnaire via the google form link. Data analysis was carried out univariate and bivariate. The results obtained in this study were that there was a relationship between participation in pregnancy exercise and the level of anxiety in third trimester primigravida mothers at BPM (Independent Practice Midwife) Widiasih, Batubulan, Gianyar